I can learn: start to read - Morgan, Nicola (Egmont London, 2000)
I Can Learn: Start to Read" is an engaging early reading resource designed to help young children develop their reading skills. Featuring simple, phonics-based text and colorful illustrations, the book encourages children to practice reading through fun and relatable stories.